Perspectives on Retail Service Quality: Findings From the Baltic States - McKenzie, Brent (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
Service quality research continues to represent one of the major tenets of Services Marketing, but there continues to be limited research in the field outside of Developed, Western markets. In order to advance the knowledge of service quality in non-western markets, the focus of this paper is to examine one particular field of service quality research, retail service quality, in the former Soviet Republics of Estonia, Latvia, and Lithuania. The testing of a model of retail service quality, using empirical survey data collected in these three recent members of the European Union, indicate support that the retail service quality construct both aligns and differs, across the three countries. The implication of these similarities and differences are important from two perspectives. The first is the appropriateness of extending Western developed marketing scales and measures within newly emerging, and catching up states. The second implication, which is important to retail practice, questions the position of treating these three countries, known collectively as the Baltic states as a homogenous market. Additional implications to retail practice and future academic research studies are also discussed.